Working inside Bank 4.0: analysing the impact of the 4IR on the organization of work in the banking sector of South Africa - Moshime, Kabelo Katlego (Rhodes University, Faculty of Humanities, Department of Sociology)
The main objective of the study is to analyse the impact of the 4IR on the organization of work processes in the banking sector of Pretoria, South Africa. The Fourth Industrial Revolution (4IR) is an extension of the digital revolution based on the interconnectedness of machinery and cyber- physical systems that intelligently produce and control production. The South African banking sector has not been immune to the changes brought on by the 4IR in other sectors, as many financial institutions in the country have digitized the bulk of their services, in order to make banking quicker and more efficient. Additionally, the latest COVID-19 pandemic has accelerated the emergence of digital solutions and e-commerce across different sectors worldwide, thus showing that 4IR is here to stay. On the surface, the adoption of various technological innovations within the banking sector seems like a logical step towards building a more efficient banking system, with minimal deficiencies and upskilling opportunities for banking employees, thus providing an improved and convenient banking experience for customers. On the other side, however, one can see general trends that may not be in the best interest for people employed within the banking sector. For example: the introduction of new technologies has reduced the number of employees in banks; the skills upgrade that some bankers have experienced as a result of new technologies, have come at the cost of the many job losses in the sector; also, the control methods in the banks have become more centralised, thus ensuring extreme monitoring of staff. Additionally, new technologies have eliminated the spaces for deficiencies, and have given consumers a greater role in their banking experiences, instead of being assisted from a-z in their local branches. In light of these changes, one has to question the real impact of these changes on the people that have chosen banking as a career, as 'machines' have taken over their banking institutions. Using the Labour Process Theory (LPT), this study examined the impact of the 4IR processes on the organization of work and the general employment experiences of employees in the banking sector of Tshwane, in the Gauteng province, of South Africa. This study found the following outcomes: technologies facilitate greater monitoring of the workplace, enable flexible specialisation for workers, reduces foot-flow in bank branches, and shifts the bankers' work into the hands of the customers.
Keywords: Industry 4.0 -- South Africa; Banks and banking -- South Africa; Banks and banking Technological innovations -- South Africa; Organizational change -- South Africa; Bank employees -- South Africa; Job security; Labour process theory